Pengaruh Job Insecurity, Kompensasi, Kepuasan Kerja Terhadap Turnover Intention - Karimah, Virda Ni’matul; Aslamiyah, Suaibatul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The success of the organization is determined, among others, by human resources because human resources are valuable and most important assets in an organization. Seeing the important role of human resources, it is necessary to pay attention to the provisions of the work system that should ensure a sense of security and comfort in the company, so that employees' intention to move or leave the company (turnover intention) will not exist. Because after all, employee companies are valuable assets in running the wheels of business operations so that the economy of a country remains stable. This research is a quantitative study with a survey method conducted at PT X East Java, involving 117 employees who were sampled with a population of 165 respondents. This study uses a Partial Least Square (PLS) based regression approach to test the relationship between variables. The results of this study indicate that job insecurity, compensation and job satisfaction have a significant positive effect on turnover intention. The practical implications emphasize the need for support and increased efforts so that turnover intention at PT. X does not occur. The management of PT. X needs to consider more effective time management strategies to overcome turnover intention.